Examination of acetabular labral tear: a continued diagnostic challenge. Issue 4 (31st July 2013) - Reiman, Michael P; Mather, Richard C; Hash, Thomas W; Cook, Chad E
Abstract : Acetabular labrum tears (ALT) are present in 22–55% of individuals with hip or groin pain. Tears can occur as a result of trauma or degeneration and are markedly associated with femoral acetabular morphological variations. An ALT can lead to biomechanical deficiencies and a loss of stability to the coxafemoral joint due to the labrum serving as a stabilising structure of this joint. The diagnosis of ALT is complex and multidimensional. Although tremendous improvements in diagnostic utility for ALT have occurred in the past 25 years, there are few patient history, clinical examination and special test findings that are unique to the condition. Imaging methods such as MRI, CT and ultrasonography have demonstrated reasonable accuracy, but not at a level that allows use as a stand-alone measure. Outcomes measures that focus on functional limitation or that are used to measure recovery should envelop the complexities of the condition and be captured using both self-report and physical performance measures. Only when patient history, objective testing, clinical examination special testing and imaging are combined can a clinician fully elucidate the multidimensional diagnosis of ALT.